Description of a new genus, Auritibicen gen. nov., of Cryptotympanini Hemiptera: Cicadidae) with redescriptions of Auritibicen pekinensis (Haupt, 1924) comb. nov. and Auritibicen slocumi (Chen, 1943) comb. nov. from China and a key to the species of Auritibicen - Lee, Young June (Zootaxa, 2015)
A new genus, Auritibicen gen. nov., is erected for the former members of Lyristes Horváth, 1926 (= Tibicen Latreille, 1825) from eastern Asia, designating Tibicen intermedia Mori, 1931 as the type species. Morphological comparisons are made among Auritibicen, Lyristes, and the American Tibicen species. Auritibicen pekinensis (Haupt, 1924) comb. nov. and Auritibicen slocumi (Chen, 1943) comb. nov. from China are redescribed. Morphological comparisons are made among closely related species, A. pekinensis, A. slocumi, Auritibicen intermedius (Mori, 1931) comb. nov., and Auritibicen kyushyuensis (Kato, 1926) comb. nov. A key to the species of the genus Auritibicen gen. nov. is provided.